Optical Properties of Porous Silicon Solar Cells for Use in Transport - Martin Kralik; Michaela Hola; Stanislav Jurecka (Communications - Scientific letters of the University of Zilina, 2019)
Porous silicon (pSi) samples were prepared by electrochemical etching of p-type silicon (p-type Si) substrate. Three pSi samples with different parameters of electrochemical etching (electrical potential, etching time, etching current) were prepared and analyzed. We studied the influence of electrochemical etching parameters on spectral reflectance of pSi structure. A modification of interference pattern was observed due to changes of microstructure. We determined the thickness of pSi layers from spectral reflectance. Solar cells with a porous structure achieve high efficiency and long life. These solar cells are predestined for use in transport.